Reporting on Environmental Innovation As a Means of Enhancing Firm Performance - Tumba, Afnei Ngan Billy (Accounting Research Unit (ARU Journal), 2025)
In recent decades, there has been a notable increase in the attention paid to environmental issues, concurrent with a growing awareness of the importance of sustainability on a global scale. Environmental innovation performance constitutes an essential element of contemporary business strategy. It is hypothesized that enhancements to environmental innovation performance may yield favorable outcomes for corporate performance. A business's profitability, operational efficiency, and reputation typically indicate its overall performance. This study aims to examine the impact of environmental innovation on organizational performance. The sample for this study was drawn from all companies listed on the Indonesia Stock Exchange (IDX) that had submitted environmental innovation reports. The method employed was purposive sampling, which was used to select the sample, and linear regression was used to analyze the results of this study. The findings indicate that environmental innovation has a significant positive effect on firm performance. The conclusions of this study can provide insight to academics and practitioners on the issue of innovation in the environment, namely that it can improve firm performance, and can provide insight for stakeholders in green investment decisions.